Spain : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2005)
This report examines the Observance of Standards and Codes on Fiscal Transparency for Spain. The assessment reveals that over the last several years, Spain has made major progress not only in macroeconomic and fiscal adjustment, but also in modernizing and strengthening its fiscal institutions and in disseminating information about the government's operations. As a result, it now fully meets or exceeds the IMF Code of Good Practices on Fiscal Transparency standards in many areas. There remain, nevertheless, certain aspects in which further progress would be desirable.